Como as condições de trabalho nas indústrias de compensado do Município de Imbituva - PR refletem na saúde das mulheres empregadas - Neiverth, Elisabeth Mônica Hasse Becker (2011)
The object of this work focuses on verifying how the working conditions in industries that manufacture plywood, located in the city of Imbituva, Parana State, reflect the health of women employed. We focused on qualitative research, linking, however, the quantitative aspects. We used the research bibliographical, documentary and field, whose instruments were semi-structured interviews, questionnaires and filling in forms, in order to profile both business and the employees, know the process of production of plywood, collect data on the work environment and health of employed women. The development of work addresses issues relevant to the theme of women's work, the protection of worker health, the specific protection to female workers, ending by showing the results based on systematic theoretical framework built.